Legal Issues on Subsidies of The Agricultural Products on WTO Frame Work - Nathasya Victoria Ruswandana (Journal of Social Science, 2021)
The WTO was founded with the main objective of building a fair and market-oriented trading system. Fair trade means free and no intervention from anywhere to regulate the market. This applies to all sectors of the economy but especially concerns the agricultural sector which is the basis of a country's defense. Various efforts have been made by the WTO in terms of making trade regulations in the agricultural sector which of course aims to realize this goal. It is well known that in order to stabilize food prices, ensure abundant food production, guarantee farmers' basic income, and in general strengthen the agricultural segment of the national economy, the government has implemented various assistance in the form of assistance to agricultural product producers in the country. This assistance is called a subsidy which can take various forms, namely in the form of tariff barriers, non-tariff barriers, tax levies, positive regulations and direct subsidies to both agricultural producers and exporters. In this study, the authors examine the legal issues regarding subsidies for agricultural products within the WTO framework. The main issue in this legal research is how the legal issues regarding subsidies for agricultural products within the WTO framework. The main objective of this legal research is to find out the legal issues regarding subsidies for agricultural products within the WTO framework. This legal research is a normative legal research in which legal sources are collected through literature study. A relatively detailed review of the content of legal issues regarding subsidies for agricultural products in the WTO framework is discussed in this paper. The results of this study indicate that agriculture is one of the important trade negotiations in the WTO through the rules contained in the AoA. Agreements to implement commitments from disciplines in the AoA, from WTO member countries, are expected to be reached by both developing and developed countries